Posterior fossa hibernoma: A rare case in unexpected location radiologically mimicking arteriovenous malformation - (:unkn) unknown (ELSEVIER SCIENCE BV, 2019)
Background: Hibernomas are rare tumors histologically originate from the fetal brown adipose tissue. Here, we reported the first hibernoma case located in posterior fossa radiologically mimicking arteriovenous malformation (AVM), presenting with abrupt onset of dizziness, and hiccups. This is the first case of hibernoma location in the posterior fossa. Case description: A previously well 32-year-old man, presented with a headache for three days and abrupt onset of dizziness, nausea, vomiting, and hiccups. He had left-sided muscle weakness and hypoesthesia. Non-contrast enhanced computed tomography revealed hemorrhagic lesion at the inferoventral portion of the posterior lobe of cerebellum with compression to medulla oblongata with partial obstruction of fourth ventricle. Magnetic Resonance Imaging (MRI) revealed a mass lesion neighbouring at medulla oblongata which had intratumoral large vessels with branching segments. On T1 weighted images the lesion was isointense, on T2 weighted images it was hyperintense. On contrast-enhanced MRI images, heterogeneous contrast pattern was observed which is highly suspicious for AVM. Emergent surgery was performed and total excision was achieved. Histopathological analysis with Hematoxylin and eosin staining revealed yellow coloured, minimal hemorrhagic areas and well-defined encapsulated solid structure. The specimen showed brown adipose tissue content, with well-defined cytoplasm, large granular or multivacuolated cytoplasmic cells. Besides, small groups of univacuolar adipocytes were also observed. The histopathologic diagnosis was typical hibernoma. The postoperative period was uneventful and the patient was discharged in the fourth postoperative day with full neurological recovery. His neurological examination at the sixth postoperative month was completely normal. Radiological evaluation revealed total excision without any recurrence. Conclusions: Hibernoma located in the posterior fossa is a unique condition, which may cause acute deterioration of the patient. These lesions may radiologically mimic vascular malformations. The neurological surgeons must kept in mind that hibernoma could also be seen in posterior fossa.